2018
DOI: 10.4314/as.v17i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Demand for formal credit among small scale cassava farmers in Kogi State, Nigeria: a double hurdle analysis

Abstract: In Nigeria, one of the major constraints to the decline in agriculture's contribution to the economy is inaccessibility to capital by small scale farmers. This study therefore examined the determinants of access and demand for formal credit by small scale cassava farmers in Okene, Okehi and Adavi Local Government Areas of Kogi State. Data were collected from 120 cassava farmers; descriptive and double hurdle model were used to analyse the data. The result of the analysis showed that the sampled farmers were yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(5 reference statements)
2
1
0
Order By: Relevance
“…The relatively high prevalence of food insecurity and hunger in Oyo was worrisome since the data were collected during a period in which food was expected to be abundant. It, however, aligns with previous studies of smallholder farmer households 40 and other households 41 in Oyo State, which reported a high prevalence of food insecurity. Adebayo (2012) reported a 53% food insecurity prevalence, 40 while Ganiyu and Omotayo (2016) reported a 29% prevalence of food insecurity among the households in one LGA of the state.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The relatively high prevalence of food insecurity and hunger in Oyo was worrisome since the data were collected during a period in which food was expected to be abundant. It, however, aligns with previous studies of smallholder farmer households 40 and other households 41 in Oyo State, which reported a high prevalence of food insecurity. Adebayo (2012) reported a 53% food insecurity prevalence, 40 while Ganiyu and Omotayo (2016) reported a 29% prevalence of food insecurity among the households in one LGA of the state.…”
Section: Discussionsupporting
confidence: 91%
“…It, however, aligns with previous studies of smallholder farmer households 40 and other households 41 in Oyo State, which reported a high prevalence of food insecurity. Adebayo (2012) reported a 53% food insecurity prevalence, 40 while Ganiyu and Omotayo (2016) reported a 29% prevalence of food insecurity among the households in one LGA of the state. 41 For access to care and health, the 2013 Nigeria Demographic and Health Survey results indicate that the households included in the NDDP study were worse off than the average household in Oyo, while those in Kano appeared better off than average.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, lack of collateral, short repayment period and high interest rates were the constraints faced in accessing formal credit. Adebayo (2018) investigated the factors responsible for demand and access to formal credit by cassava farmers in Kogi state, Nigeria. The results revealed that farm income, farming experience and farm size were responsible for cassava farmers’ access to formal credit.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%